Physicians' professional autonomy and their organizational identification with their hospital - Domenico Salvatore; Dino Numerato; Giovanni Fattore (BMC, 2018)
Abstract Background Managing medical professionals is challenging because professionals tend to adhere to a set of professional norms and enjoy autonomy from supervision. The aim of this paper is to study the interplay of physicians' professional identity, their organizational identity, and the role of professional autonomy in these processes of social identification. Methods We test hypotheses generated according to social identity theory using a survey of physicians working in public hospitals in Italy in 2013. Results Higher degrees of organizational and economic professional autonomy are correlated with higher organizational identification. Identification with the profession is positively correlated with identification with the organization. Conclusions Although the generalizability of our results is limited, this study suggests that organizations should support the organizational and economic autonomy of their physicians to project an organizational identity that preserves the continuity of a doctor's self-concept and that is evaluated as positive by doctors. As a result, organizations will be able to foster organizational identification, which is potentially capable of inducing pro-social organizational behavior.